Heat transfer across the dynamics of water conveying alumina nanoparticles subject to Lorentz force in a rectangular cavity with various aspect ratios - Bahreini, Sayed Hamid; Saghafian, Mohsen; Akbari, Omid Ali (Journal of thermal analysis and calorimetry, 2023)
Heat transfer in cavities under the influence of magnetic field is very important in industry. The effect of the presence of a magnetic field on the behavior of heat transfer in closed cavities (electrical transformers) is inevitable, which is addressed in this research. The present study is about the heat transfer of water/alumina nanofluid in a rectangular cavity. The cavity has two insulated walls in front of each other, a constant temperature warm wall at an angle of zero with the horizontal and a constant temperature cold wall. A constant magnetic force with Hartmann number of Ha = 0–45 is applied, which has a zero angle with respect to the horizontal line. The Rayleigh number is Ra = 10 5 , and the problem is solved for various length-to-width cavity aspect ratios of AR = 1–6. In this paper, the solution method uses a finite volume discretization with a pressure-based and segregated algorithm. Results revealed that for AR = 1, the temperature contours have a decreasing trend from top to bottom, as it experiences the maximum and minimum temperatures near the warm and cold walls. For this aspect ratio, the minimum dimensionless temperature occurs at the dimensionless position of X = 0.7–0.8 for various Hartmann numbers, which also coincides with the maximum Nusselt number. For the aspect ratio of AR = 2, increasing the magnetic force results in a higher Lorentz force, which opposes the buoyancy force, reducing the local Nusselt number. However, for AR = 4, increasing the magnetic force creates straight isothermal lines. For this aspect ratio, the isothermal lines are close to each other near the warm wall at two points of X = 0.3 and 0.7, with a slight temperature difference, thereby maximizing the Nusselt number. For AR = 6 and all Hartmann numbers, the Nusselt number is maximum at two points of X = 0.34 and 0.65, while the minimum is located at X = 0.2, 0.5, and 0.8.